Pelatihan Kesantunan Linguistik dan Kesantunan Pragmatik Tuturan Imperatif pada Siswa SD Negeri Binaan Khusus Dumai Timur - Fatmawati, Fatmawati; Apriani, Leni; Ningsih, Rika; Fiansyah, Wahyu; Widyawati, Kiki (UIR Press, 2026)
Ideally, imperative speech is delivered in the most polite language. This is because in the imperative speech there is a desire for others to be willing to do something intended in a speech. Through the use of polite language, it is hoped that the governed party will not feel offended by the speech conveyed. However, the reality in society shows the fact that children are contaminated with inappropriate speech patterns. This is influenced by a number of factors, including educational background, economy, social environment, and family environment. The solution offered to increase student awareness in applying imperative politeness is to conduct training in linguistic politeness and imperative pragmatic politeness. The results of this PkM show that there is an increase in students' understanding in applying language politeness to imperative speech. Broadly speaking, students prefer to use pragmatic politeness over linguistic politeness. In pragmatic politeness, the dominant criterion used is imperative pragmatic politeness in interrogative speech. Meanwhile, linguistic politeness is conveyed through the short length of speech, the order of speech, and the use of expressions marking politeness. Imperative entities are ensured to be always present in learning activities in the classroom and outside the classroom. Therefore, teachers should also maximize the use of polite imperatives when communicating with students.